2019
DOI: 10.1017/wet.2019.53
|View full text |Cite
|
Sign up to set email alerts
|

Common evening-primrose (Oenothera biennis L.)

Abstract: Primroses, The spring may love them; Summer knows but little of them. Foresight. William Wordsworth, 1819 Ring-ting! I wish I were a Primrose A bright yellow Primrose, blowing in the Spring! Wishing. William Allingham "The snowdrop and primrose our woodlands adorn, and violets bathe in the wet o' the morn." Robert Burns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Administration of OBS-E at a concentration of 50 or 200 mg/kg BW once a day for 14 weeks was well-tolerated and no abnormal signs or significant changes in body weight changes were observed, thus indicating that the administration schedule and doses were safe. These results are consistent with those of a previous report which reported that O. biennis administration is not associated with any toxicity issues [ 20 ]. Significant differences were observed in all parameters measured for the UVB-irradiated control group compared with those for the non-irradiated control group, demonstrating that our UVB irradiation process induced damage in the mice.…”
Section: Discussionsupporting
confidence: 93%
“…Administration of OBS-E at a concentration of 50 or 200 mg/kg BW once a day for 14 weeks was well-tolerated and no abnormal signs or significant changes in body weight changes were observed, thus indicating that the administration schedule and doses were safe. These results are consistent with those of a previous report which reported that O. biennis administration is not associated with any toxicity issues [ 20 ]. Significant differences were observed in all parameters measured for the UVB-irradiated control group compared with those for the non-irradiated control group, demonstrating that our UVB irradiation process induced damage in the mice.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, our study only captured bumble bee choice for plant species visited during the period of 10:00-16:00, eliminating observations of visits to species that specialize in attracting pollinators outside these hours. For example, Mimulus ringens (Christopher et al, 2021) and Tradescantia ohiensis (Parrish & Bazzaz, 1979) receive most visits before 10:00, while Oenothera opens late in the day (Steckel et al, 2019). Therefore, a strong knowledge of the natural history of individual plant species should inform planting decisions.…”
Section: How Does Bumble Bee Flower Selection Vary Across the Growing...mentioning
confidence: 99%
“…An example is now given to illustrate the object selection process. First, an Oenothera biennis, also known as the common evening-primrose (Steckel et al 2019), represents dusk and therefore the time when the lights should be turned on. Conversely, the user decides to use a sunflower (Kutschera and Briggs 2016) to represent dawn and thus the time when the lights should be turned off.…”
Section: Time To Switch the Lightsmentioning
confidence: 99%